2007
DOI: 10.1007/s11274-007-9602-5
|View full text |Cite
|
Sign up to set email alerts
|

Allelopathic impact of artificially applied coumarin on Fusarium oxysporum f.sp. niveum

Abstract: Watermelon production is threatened by fusarium wilt caused by Fusarium oxysporum f.sp. niveum (FON) in continuous cultivation system. Some elements, mainly allelochemicals, released from living roots or decayed plants might be associated with the disease. The purpose of this work was to evaluate the possible impact of coumarin, one kind of watermelon allelochemical, on FON. Furthermore, possible new mechanisms might be investigated during the ecological interactions of plant-microbe. Results showed that couma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0
3

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(20 citation statements)
references
References 44 publications
1
16
0
3
Order By: Relevance
“…Wu et al . (2008a,b,c) showed that cinnamic acid, coumaric acid or vanillic acid, when applied to F. oxysporum f. sp. niveum cultures, increased mycotoxin production (probably predominantly fusaric acid) and the activity of hydrolytic enzymes, such as pectinase, cellulose and amylase (only in the presence of cinnamic and vanillic acids).…”
Section: Overcoming Plant Defence Responsesmentioning
confidence: 99%
“…Wu et al . (2008a,b,c) showed that cinnamic acid, coumaric acid or vanillic acid, when applied to F. oxysporum f. sp. niveum cultures, increased mycotoxin production (probably predominantly fusaric acid) and the activity of hydrolytic enzymes, such as pectinase, cellulose and amylase (only in the presence of cinnamic and vanillic acids).…”
Section: Overcoming Plant Defence Responsesmentioning
confidence: 99%
“…The conidial suspension of FON was diluted to no more than 1000 conidia per milliliter with sterile distilled water. The diluted suspension (0.1 ml) was spread on Petri-plates containing 2% water agar and incubated at 28°C for 3 d. The number of colonies was counted after 3 d of incubation (Wu et al 2008b). …”
Section: Assessment Of Root Exudates On Conidial Germinationmentioning
confidence: 99%
“…In this respect, Muhsin et al (2001) reported high reductions in the activities of amylase, cellulase and protease for A. flavus, A. alternate and other 16 fungal species subjected to garlic extract in the growth medium. Furthermore, Wu et al (2008) demonstrated that the artificially applied coumarin inhibited the activity of protease, amylase and cellulase of F. oxysporum. In addition, Fawzi et al (2009) reported that cinnamon, halfa barr, laurel, avocado and ginger extracts inhibited the production of glucosidase, pectin lyase and protease by A. alternata and F. oxysporum.…”
Section: Resultsmentioning
confidence: 99%
“…Total amylase activity was assayed according to DNS method (Wu et al, 2008). The mixture contained 100 µl of the above prepared filtrate, 2 ml of 0.15 M citrate-phosphate buffer (pH 5.0) and 3 ml of 4% (w/v) soluble starch previously maintained at 40°C for 15 min.…”
Section: Amylase Activity Assaymentioning
confidence: 99%